Terraplén análisis de carga bajo condiciones de laboratorio (2011)
The embankment model has been developed in laboratory conditions, considering actual embankment characteristics. The forces to which it is subjected in the model have been evaluated using shaking table experimental and analytical methods. Excess pore water pressure is measured through pore pressure sensors in the shaking table experiment and embankment stability has been assessed using analytical methods. The results revealed that the embankment suffered nonlinear collapse during increasing pore water pressure, and shaking table dynamic force on the embankment model was very sensitive but was open to failure mitigation. Embankment seismic simulation using shaking table experiments helped identify model stability. The embankment and subsoil pore water pressure theoretical and experimental analysis concluded that nonlinear liquefaction characteristics played a major role in model behaviour.